Tidal in-stream energy density estimates for pre-identified sites in the Philippines using a tide height difference-based metric - Ang, Ma. Rosario Concepcion O. (2013)
The Philippines, being an archipelagic country, is well known for its relatively strong and persistent currents in its straits and channels. Harnessing these strong currents for tidal in-stream energy will greatly help reduce the dependency of the country to imported oil for power generation. The developed energy potential (EP) metric was validated using sites identified by the Philippines' Department of Energy (DOE) as having high potential for ocean tidal energy. This metric provides a less complex methodology with acceptable accuracy for tidal in-stream resource assessment that makes use of tide height difference at the boundaries of a channel. Using this enables geographic information system (GIS) based data to increase turn-around time for site suitability, technology matching, and feasibility studies for ocean renewable energy installations.